Investigations of Koutango Virus Infectivity and Dissemination Dynamics in Aedes aegypti Mosquitoes - de Araújo Lobo, Jaime M (Environ Health Insights, 2014)
Aedes aegypti has already been implicated in the emergence of dengue and chikungunya viruses in the southern US. Vector competence is the ability of a mosquito species to support transmission of an arbovirus, which is bounded by its ability to support replication and dissemination of the virus through the mosquito body to the salivary glands to be expectorated in the saliva at the time of feeding on a vertebrate host. Here, we investigate the vector competence of A. aegypti for the arbovirus koutango by orally challenging mosquitoes with two titers of virus. We calculated the effective vector competence, a cumulative measure of transmission capability weighted by mosquito survival, and determined that A. aegypti was competent at the higher dose only. We conclude that further investigation is needed to determine the infectiousness of vertebrate hosts to fully assess the emergence potential of this virus in areas rich in A. aegypti.